Habitat, latitude and body mass influence the temperature dependence of metabolic rate. (31st August 2018) - DeLong, J. P.; Bachman, G.; Gibert, J. P.; Luhring, T. M.; Montooth, K. L.; Neyer, A.; Reed, B.
Abstract : The sensitivity of metabolic rate to temperature constrains the climate in which ectotherms can function, yet the temperature dependence of metabolic rate may evolve in response to biotic and abiotic factors. We compiled a dataset on the temperature dependence of metabolic rate for heterotrophic ectotherms from studies that show a peak in metabolic rate at an optimal temperature (i.e. that describe the thermal performance curve for metabolic rate). We found that peak metabolic rates were lower in aquatic than terrestrial habitats and increased with body mass, latitude and the optimal temperature. In addition, the optimal temperature decreased with latitude. These results support competing hypotheses about metabolic rate adaptation, with hotter being better in the tropics but colder being better towards the poles. Moreover, our results suggest that the temperature dependence of metabolic rate is more complex than previously suggested.